SEREX identification of new tumour-associated antigens in cutaneous T-cell lymphoma - Hartmann, Tanja B.; Schadendorf, Dirk; Eichmüller, Stefan B. (British journal of dermatology, 2004)
Background: Cutaneous T-cell lymphoma (CTCL) is a clonal lymphoproliferative disorder of mainly CD4+ T cells, with primary manifestation in the skin. Objectives To detect new CTCL-associated antigens for immunological therapies and to define their specificity in terms of RNA expression and seroreactivity. Methods: A newly constructed CTCL cDNA phage library was screened and cross-reactivities against the detected clones were tested using 15 mycosis fungoides and six Sézary syndrome sera. The mRNA expression of the identified genes was analysed by reverse transcription-polymerase chain reaction (RT-PCR) using 22 tumour tissues, nine cell lines and up to 29 different types of normal tissue. Results: We identified nine different tumour antigens (HD-CL-01 to HD-CL-09) of which seven clones had high homology to genes with known functions. Several of these genes had previously been associated with cancer, namely inositol 1,4,5-triphosphate 5-phosphatase, vimentin, aldose reductase and elongation factor-1α. Variations in the deduced protein sequences were observed in three cases, mostly due to variations in protein length. The individual clones were recognized by up to 56% of patients' sera, while control sera were negative except in one case. Using RT-PCR, we found a frequent expression of these new tumour antigens in tumour specimens (26-100%). In contrast to humoral specificity, specific mRNA was also detected in selected normal tissues (29-89%). Conclusions: SEREX (serological identification of antigens by recombinant expression cloning) identified multiple tumour-associated antigens in CTCL. The serological specificity and the high percentage of reactive sera of CTCL patients against several clones suggest these genes as potential targets for diagnostic and prognostic purposes.